Bronchial atresia of the right lower lobe - Murat, A; Ozdemir, H; Yildirim, H; Poyraz, AK; Artas, H (Taylor & Francis Ltd, 2005)
Bronchial atresia ( BA) is a rare congenital anomaly that is found incidentally in approximately 50% of cases. It predominantly affects young men and generally produces no symptoms. The other 50% of cases have pulmonary symptoms such as fever, cough, or shortness of breath due to recurrent pulmonary infection or overinflation of the involved lung parenchyma. The most common site is the left upper lobe, particularly of the apical-posterior segment. The right lower and middle lobes are affected in only 8% of cases. The radiographic features may be highly suggestive of the diagnosis. The mucus-filled bronchus is seen as a rounded, branching opacity emanating from the hilum and is surrounded by an area of increased hyper-translucency. We report an unusual presentation of BA in a 43-year-old woman with a history of recurrent pulmonary infection and dyspnea. The patient was found to have BA in all the basal segments of the lower lobe of the right lung.
Keywords: bronchial atresia; chest CT; chest MRI; chest radiography